The municipal power in the aspect of the electoral rights of the voters - Новак, О. М. (Problems of legality, 2014)
This article examines some of the problems, connected mainly with the development of human ideas about the municipal authorities in the historical and legal context. Covers the basic form of democracy that have existed for human development at the local level. Discusses the different types of electoral systems in different European countries. It turns out the question of what electoral system is optimal for the local elections for modern Ukraine.